A decade of advances in the study of buckwheat for organic farming and agroecology (2013-2023) - Vieites-Álvarez, Yedra; Reigosa, Manuel J.; Sánchez-Moreiras, Adela M. (Frontiers in Plant Science, 2024)
During the last decade, research has shown the environment and human health benefits of growing buckwheat (Fagopyrum spp.). This comprehensive review aims to summarize the major advancements made in the study of buckwheat from 2013 to 2023, focusing on its agronomic characteristics, nutritional value, and potential applications in sustainable agriculture. The review examines the diverse applications of buckwheat in organic and agroecological farming systems, and discusses the ability of buckwheat to control weeds through allelopathy, competition, and other sustainable farming methods, such as crop rotation, intercropping and green manure, while improving soil health and biodiversity. The review also explores the nutritional value of buckwheat. It delves into the composition of buckwheat grains, emphasizing their high protein content, and the presence of essential amino acids and valuable micronutrients, which is linked to health benefits such as lowering cholesterol levels, controlling diabetes and acting against different types of cancer, among others. Finally, the review concludes by highlighting the gaps in current knowledge, and proposing future research directions to further optimize buckwheat production in organic or agroecological farming systems. It emphasizes the need for interdisciplinary collaboration, and the integration of traditional knowledge with modern scientific approaches to unlock the full potential of buckwheat as a sustainable crop.